PAME Work Plan 2011-2013. - Protection of the Arctic Marine Environment (PAME) (Arctic Council Secretariat, 2011)
Arctic Council working group Protection of the Arctic Marine Environment (PAME)s work plan for the years 2011-2013, presented at the Arctic Council's Senior Arctic Officials meeting in Copenhagen, Denmark, March 16-17 2011 prior the Ministerial Meeting in Nuuk, Greenland, later the same year.